Obtenção de polímeros graftizados de quitosana e estudo das propriedades físico-químicas para aplicação na indústria do petróleo - Alves, Keila dos Santos (2013)
Chitosan is a biopolymer derived from the shells of crustaceans, biodegradable, inexpensive and renewable with important physical and chemical properties. Moreover, the different modifications possible in its chemical structure generate new properties, making it an attractive polysaccharide owing to its range of potential applications. Polymers have been used in oil production operations. However, growing concern over environmental constraints has prompted oil industry to search for environmentally sustainable materials. As such, this study sought to obtain chitosan derivatives grafted with hydrophilic (poly(ethylene glycol), mPEG) and/or hydrophobic groups (n-dodecyl) via a simple (one-pot) method and evaluate their physicochemical properties as a function of varying pH using rheology, small-angle Xray scattering (SAXS), dynamic light scattering (DLS) and zeta potential. The chitosan derivatives were prepared using reductive alkylation under mild reaction conditions and the chemical structure of the polymers was characterized by nuclear magnetic resonance (1H NMR) and CHN elemental analysis. Considering a constant mPEG/Chitosan molar ratio on modification of chitosan, the solubility of the polymer across a wide pH range (acidic, neutral and basic) could only be improved when some of the amino groups were submitted to reacetylation using the one-pot method. Under these conditions, solubility is maintained even with the simultaneous insertion of n-dodecyl. On the other hand, the solubility of derivatives obtained only through mPEG incorporation using the traditional methodology, or with the ndodecyl group, was similar to that of its precursor. The hydrophilic group promoted decreased viscosity of the polymer solutions at 10 g/L in acid medium. However, at basic pH, both viscosity and thermal stability increased, as well as exhibited a pronounced pseudoplastic behavior, suggesting strong intermolecular associations in the alkaline medium. The SAXS results showed a polyelectrolyte behavior with the decrease in pH for the polymer systems. DLS analyses revealed that although the dilute polymer solutions at 1 g/L and pH 3 exhibited a high density of protonated amino groups along the polymer chain, the high degree of charge contributed significantly to aggregation, promoting increased particle size with the decrease in pH. Furthermore, the hydrophobic group also contributed to increasing the size of aggregates in solution at pH 3, whereas the hydrophilic group helped reduce their size across the entire pH range. Nevertheless, the nature of aggregation was dependent on the pH of the medium. Zeta potential results indicated that its values do not depend solely on the surface charge of the particle, but are also dependent on the net charge of the medium. In this study, water soluble associative polymers exhibit properties that can be of great interest in the petroleum industry